Student experience scale: Factor analysis in higher education institutions - Amado Mateus, Marelby; Guzmán Rincón, Alfredo; Cuero Acosta, Yonni Angel (Frontiers in Education, 2023)
In the context of higher education, the student experience (SX) has an important impact on student satisfaction and the perceived value of the training service received. For these reasons, higher education institutions (HEIs), which are focused on student-centred learning, need to know more about the experience that results from student interaction with the service and support systems that meet their needs in these institutions. However, despite the progress made in the analysis of SX, further research is still needed to know how to measure and manage it, and for this, it is essential to know the student's perceptions. For this reason, an SX scale was selected to have a suitable tool for experience management. Thus, the psychometric properties of the selected scale were evaluated in undergraduate students at two Colombian universities. The validation process consisted of an adaptation of the scale, a content validity analysis, an exploratory factor analysis and a confirmatory factor analysis. The results were satisfactory showing the reliability and validity of the student experience scale in the context of universities.